2016
DOI: 10.1002/app.43988
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of hydrophilic and antifouling poly(ether sulfone) ultrafiltration membranes modified with Zn–Al layered double hydroxides

Abstract: Zn-Al layered double hydroxide (LDH)-entrapped poly(ether sulfone) (PES) ultrafiltration membranes with four different weight percentages, 0.5, 1.0, 2.0, and 3.0%, were prepared by a phase-inversion method. Characterization by scanning electron microscopy, atomic force microscopy and contact angle (CA), equilibrium water content, porosity, average pore size, mechanical strength, and f potential measurement were used to evaluate the morphological structure and physical and chemical properties of membranes. Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…Increase in the NPs loading enhances membrane hydrophilicity (reflected by lower apparent contact angle Figure 2a,b) and increases EWC. The same observation was found by Yu Zhao et al [29] It has been observed that EWC of SiO 2 or TiO 2 modified PAN membrane is always higher than that of PVDF membrane, which is due to inherent hydrophilicity of PAN than PVDF. From Figure 1a it is observed that the initial EWC for PAN membrane is 79% and that of PVDF membrane is 70%.…”
Section: Equilibrium Water Contentsupporting
confidence: 84%
“…Increase in the NPs loading enhances membrane hydrophilicity (reflected by lower apparent contact angle Figure 2a,b) and increases EWC. The same observation was found by Yu Zhao et al [29] It has been observed that EWC of SiO 2 or TiO 2 modified PAN membrane is always higher than that of PVDF membrane, which is due to inherent hydrophilicity of PAN than PVDF. From Figure 1a it is observed that the initial EWC for PAN membrane is 79% and that of PVDF membrane is 70%.…”
Section: Equilibrium Water Contentsupporting
confidence: 84%
“…Due to their highly tunable properties and unique anion exchange properties, LDHs are considered as a new emerging and the most favorable class of layered crystals for fabricating of multifunctional polymer/layered inorganic nanocomposites. 1,11,12 However, the integrated hydrogen-bonding networks and the strong electrostatic interactions between hydroxide layers and intercalated anions/water molecules, which results from the high charge density of LDH layers associated with a high content of intercalated hydrated anions, make the intercalation or exfoliation very difficult in polymer matrix. This may explain the reason for the relatively less reported LDHs-based nanocomposites.…”
Section: + (Oh) 2 ]mentioning
confidence: 99%
“…In recent years, polymer/layered crystal nanocomposites have been recognized as one of the most promising polymer composites due to their remarkably improved mechanical performances, thermal stability, ammability, gas barrier properties, and other physico-chemical properties by addition of only a small amount of layered llers. [1][2][3][4] Such an improvement is hard to be achieved by blending llers of micrometer particle size with the polymers. In the past several years, most emphases have been given to polymer layered silicate nanocomposites, 5 such as polymer/montmorillonite system.…”
Section: Introductionmentioning
confidence: 99%
“…The polymeric matrix can be controllled by adding polymeric additives such as Poly vinyl pyrrolidone (PVP) and poly ethylene glycol (PEG) [19][20][21][22]. Furthermore, by acting as a pore-former and reducing macrovoids, PVP has been shown to play a significant role in improving membrane hydrophilicity and flow [23,24].…”
Section: Introductionmentioning
confidence: 99%